Learning from Trades. (24th May 2017) - Mauring, Eeva
Abstract : I study stationary cut‐off‐strategy equilibria of a dynamic market model where buyers sample sellers sequentially from an unknown distribution. Buyers learn about the distribution from the sampled sellers and a 'trade signal'. The trade signal reveals whether a randomly chosen seller traded yesterday. Observing a trade (as opposed to no trade) is good news about the distribution. Buyers who observe a trade use a higher cut‐off than buyers who observe no trade, despite buyers' learning from sampled sellers that puts a countervailing pressure on the cut‐offs. The trade signal may reduce market efficiency, while an appropriate exogenous signal increases efficiency.